Revealing the Impact of Different Iron‐Based Precursors on the 'Catalytic' Graphitization for Synthesis of Anode Materials for Lithium Ion Batteries. Issue 5 (13th January 2023) - Frankenstein, Lars; Glomb, Pascal; Ramirez‐Rico, Joaquin; Winter, Martin; Placke, Tobias; Gomez‐Martin, Aurora
Abstract: Low cost and environmentally friendly production of graphite anodes from naturally available biomass resources is of great importance to satisfy the increasing material demand for lithium ion batteries. Herein, graphitization of coffee ground was performed using four different iron‐based activating additives, including iron (III) chloride, iron (III) nitrate, iron (III) oxide and pure iron, following either a wet or a dry mixing approach. The structural development regarding the type of activator used and the impact on the corresponding electrochemical performance are systematically investigated. A maximum degree of graphitization between 55 and 74 % (as determined by Raman spectroscopy) is attained using iron (III) chloride and iron powder, respectively. The graphitic anode material synthesized using iron powder reached a maximum reversible capacity of ≈320 mAh g −1 at a rate of 0.1 C. This study provides significant insights into the impact of activators on the design of synthetic graphite from renewable sources. Abstract : Catalytic Graphitization for Lithium Ion Batteries : 'Catalytic graphitization' allows for the transition of sustainable biomass resources to synthetic graphite anode materials for lithium ion batteries. Herein, the efficiency of different iron‐based activators (iron (III) chloride, iron (III) nitrate, iron (III) oxide and pure iron) at a fixed concentration is investigated with regard to structural development as well as electrochemical performance in carbon || Li metal cells.